2021
DOI: 10.2166/wst.2021.050
|View full text |Cite
|
Sign up to set email alerts
|

Coconut shell derived ZnCl2 activated carbon for malachite green dye removal

Abstract: The coconut-based agricultural wastes have gained wide attention as an alternative adsorbent for the removal of diverse pollutants from the industrial effluents. This paper presents the zinc chloride activation of adsorbent carbon and the utilization as an adsorbent for the removal of malachite green dye from aqueous solution. The characterisation of activated carbon was performed to get an insight into the adsorption mechanism. The ZnCl2 activated carbon acquired a higher specific surface area (544.66 m2 g−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…The produced activated carbon presented a micro/mesoporous structure. The microporous and mesoporous structures were according to the research conducted by Piriya et al (2021) , which produced activated carbon from coconut shells and chemical activation using ZnCl 2 aiming at the removal of malachite green dye from aqueous solutions. In addition, these structures were on par with the results found by Wang et al (2013) , a study aiming the optimization of mesoporous activated carbon produced from coconut shells and activation with H 3 PO 4 , which also identified mainly microporous (total volume of 37.06%) and mesoporous (total volume of 62.85%) structure formed.…”
Section: Resultsmentioning
confidence: 99%
“…The produced activated carbon presented a micro/mesoporous structure. The microporous and mesoporous structures were according to the research conducted by Piriya et al (2021) , which produced activated carbon from coconut shells and chemical activation using ZnCl 2 aiming at the removal of malachite green dye from aqueous solutions. In addition, these structures were on par with the results found by Wang et al (2013) , a study aiming the optimization of mesoporous activated carbon produced from coconut shells and activation with H 3 PO 4 , which also identified mainly microporous (total volume of 37.06%) and mesoporous (total volume of 62.85%) structure formed.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, wastewater treatment is essential and various technologies have been employed for dye removal such as electrocoagulation; photocatalytic, oxidative, and biochemical degradation; and adsorption. Adsorption has received special attention due to its simplicity, high efficiency, including the treatment of concentrated dye effluents, low cost, and the possibility of reusing the adsorbent through its recovery and regeneration [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal et al [4] reported the two-step process as the most effective due to the high porosity developed: (1) carbonization of the material under an inert atmosphere which enables the removal of moisture, volatile compounds, and other aromatic and then resulting in a char with high carbon content; and (2) activation at elevated temperature to degrade the cellulosic materials in the precursor and to attain specific characteristics which will depend on the process conditions used. Carbonization depends on several factors such as the existence of an inert atmosphere, the heating rate, the carbonization temperature, and time [5,10]. The resulting char can be activated through chemical activation that could be performed by impregnation (wet oxidation) or by mixing the char with the solid activating agent (dry oxidation) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the obliterations of the quality of air, water, and soil which are critical for life sustenance on earth are due to the fast-growing global population and industrialization [5]. An imperative constraint for economic growth is the accelerated urbanization and industrialization as well as the swift increase in water consumption and the issue of water scarcity [6].…”
Section: Introductionmentioning
confidence: 99%